Optimizing the geometry of aerodynamic lens injectors for single‐particle coherent diffractive imaging of gold nanoparticles. Issue 6 (16th November 2021) - Worbs, Lena; Roth, Nils; Lübke, Jannik; Estillore, Armando D.; Xavier, P. Lourdu; Samanta, Amit K.; Küpper, Jochen
Abstract : An optimization procedure of an aerodynamic lens injector with variable geometry is presented. The simulation results are validated by performing experiments on gold and sucrose nanoparticles. This work is envisioned to be an important step towards high‐resolution single‐particle imaging. Abstract : Single‐particle X‐ray diffractive imaging (SPI) of small (bio‐)nanoparticles (NPs) requires optimized injectors to collect sufficient diffraction patterns to allow for the reconstruction of the NP structure with high resolution. Typically, aerodynamic lens‐stack injectors are used for NP injection. However, current injectors were developed for larger NPs (>100 nm), and their ability to generate high‐density NP beams suffers with decreasing NP size. Here, an aerodynamic lens‐stack injector with variable geometry and a geometry‐optimization procedure are presented. The optimization for 50 nm gold‐NP (AuNP) injection using a numerical‐simulation infrastructure capable of calculating the carrier‐gas flow and the particle trajectories through the injector is also introduced. The simulations were experimentally validated using spherical AuNPs and sucrose NPs. In addition, the optimized injector was compared with the standard‐installation `Uppsala injector' for AuNPs. Results for these heavy particles showed a shift in the particle‐beam focus position rather than a change in beam size, which results in a lower gas background for the optimized injector. Optimized aerodynamic lens‐stack injectors will allow one to increase NP beam density, reduce the gas background, discover the limits of current injectors and contribute to structure determination of small NPs using SPI.